Molten-salt synthesis of rare-earth nickelate electronic transition semiconductors at medium high metastability. (15th January 2022) - Li, Ziang; Yan, Fengbo; Li, Xiaoyu; Cui, Yuchen; Wang, Vei; Wang, Jiaou; Liu, Chen; Jiang, Yong; Chen, Nuofu; Chen, Jikun
Abstract: The metastable rare-earth nickelates (RENiO3 ) exhibit exceptional complex electronic phase diagram and widely tunable metal to insulator transition (MIT) properties among the correlated oxide semiconductors. Unlike the synthesis of PrNiO3, NdNiO3, and SmNiO3 at low metastability, the material growth of RENiO3 with small rare-earth radius and large metastability yet requires harsh conditions. Herein, we demonstrate the molten-salt synthesis of EuNiO3 and GdNiO3 powders that reduces the oxygen pressure from the previous 90 MPa magnitude to 10 MPa utilizing their heterogeneous nucleation with KCl. The KCl behaves as seed crystal that triggers heterogeneous growth of metastable RENiO3 via interfacial energy, as confirmed by density functional theory (DFT) calculations. Apart from extending the widely adjustability in their MIT temperature ( T MIT ), we highlight the much smaller electronic resistivity of the insulating phase of RENiO3 compared to conventional thermistor materials, and this may cater for special thermistor applications such as inrush current limiting. Graphical abstract: Image, graphical abstract